A interprofissionalidade na formação em residências em saúde: perspectivas e práticas dos residentes - Costa, Nathália Gregório da (2023)
Interprofessionality occurs when professionals from different areas work mutually in order to promote comprehensive care to a person or a community through knowledge interaction. All the actors involved in qualified workforce for interprofessional work must comprehend the importance and the impact of supporting teaching actions in the service, considering the developing collaborative practices in the production of health care. In this context, this research aimed to understand the elements of interprofessionality in the health education process in two Health Residencies, from the perspective of residents. A qualitative, exploratory and descriptive research was developed. The participants of this research were nine residents from two residency programs, one multiprofessional in public health and in Family and Community Medicine. For data collection, semi-structured interviews were conducted, which were recorded and transcribed later. The field diary was also used as an instrument for the production of empirical material. Data were analyzed according to Bardin's theory of content analysis, then they were arranged in four thematic categories and subcategories. According to the research participants, there are still some obstacles in the implementation of interprofessionality in the training process in residencies. They pointed out weaknesses from the residency programs, especially in the lack of moments of Permanent Education in health for the interprofessional work. However, the residents found a conducive environment to collaborative work in the services where they were inserted. This made teamwork possible during the activities and contributed to the development and improvement of interprofessional skills of the residents. The results also indicated that the consolidation of residency programs in regions such as the Sertão of Paraíba (Northeast Region of Brazil) is a great advance in the provision of qualified care, but it needs greater integration between the offering institution and the municipal managers in order to clarify the role of the resident within the service. The pandemic moment in which the residents developed their activities may have influenced the results of this study, since considerable changes were necessary in the work process during this period. Therefore, more research should be done seeking to deepen the theme of Interprofessional Education in Health Residencies programs, since interprofessionality has currently been seen as an essential element in comprehensive health care, centered on the patient.